Respuesta :

Answer:

(3,1)

Step-by-step explanation:

Since both equations are equal to y, we can set them equal to each other

y = 3x-8

y = 4-x

3x-8 = 4-x

Add x to each side

3x+x-8 = 4-x+x

4x-8 = 4

Add 8 to each side

4x-8+8 = 4+8

4x = 12

Divide each side by 4

4x/4 =12/4

x=3

Now we can find y

y = 4-x

y = 4-3 =1

Answer: y = 3x-8

y = 4-x

3x-8 = 4-x

Add x to each side

3x+x-8 = 4-x+x

4x-8 = 4

Add 8 to each side

4x-8+8 = 4+8

4x = 12

Divide each side by 4

4x/4 =12/4

x=3

Now we can find y

y = 4-x

y = 4-3 =1

Step-by-step explanation: